Instrumen Penentu Daya Serap Tenaga Kerja Dan Strategi Peningkatannya Pada Pada Industry Kecil Di Kota Jambi - Yuvanda, Sesraria; Rachmad R, Muhammad; Aisyah RJ Nur, Deby; Ferzi, Noviardi (Jurnal Paradigma Ekonomika, 2024)
This study aims to identify the dominant instrument in determining labor absorption and its improvement strategy in small industries in Jambi City. The method used in this study is secondary data analysis, with a multiple regression model approach to analyze the relationship between variables that affect labor absorption in small industries. The data used includes information related to production, labor, and other supporting factors in the small industry sector in Jambi City. The results of the analysis show that production value is the most dominant instrument in determining labor absorption in small industries. This shows that the higher the production value, the more labor is absorbed by the small industry. Based on these findings, the strategy to increase labor absorption needs to be focused on efforts to increase production value. One approach that can be applied is to develop more efficient and productive production techniques, and improve product quality in order to compete in a wider market. In addition, it is important to pay attention to the aspect of competitive selling prices so that products from small industries can be more easily accepted by consumers.